Analisis Ujaran Kebencian Terhadap Prabowo Pada Akun Kaskus @Fufufafa: Kajian Linguistik Forensik - Khasanah, Uswatun (Kajian Linguistik dan Sastra, 2024)
This study aims to analyze and find the form of hate speech in the Kaskus account @fufufafa using a forensic linguistic perspective. This study focuses on tweets or comments posted by the Kaskus account @fufufafa regarding political issues that lead to Prabowo Subianto and his family. This type of research is descriptive qualitative using forensic linguistic methods to examine the meaning of speech semantically, understand the context and intent of speech pragmatically, and relate its relevance to legal regulations. The data in this study are in the form of words, phrases and sentences on the Kaskus account @fufufafa. The results of the study found 58 data identified as containing hate speech in the form of insults, defamation, and provocation, which use linguistic forms such as curses/invectives, satire, taboo/sarcasm. Based on semantic analysis, @fufufafa's tweets contain negative meanings, while pragmatically @fufufafa's tweets show an illocutionary intention of attack aimed at demeaning and insulting Prabowo Subianto. The most dominant form of hate speech is the category of insults that attack Prabowo Subianto's personal status, family, physical, and religious aspects. Based on the analysis that has been carried out, @fufufafa's tweet could potentially have legal consequences under Article 310 of the Criminal Code and Article 28 (2) of the ITE Law. Abstrak Penelitian ini bertujuan untuk menganalisis bentuk ujaran kebencian dalam akun Kaskus @fufufafa menggunakan perspektif linguistik forensic. Penelitian ini berfokus pada cuitan atau komentar yang diposting oleh akun Kaskus @fufufafa mengenai isu politik yang mengarah pada Prabowo Subianto dan keluarganya. Jenis penelitian ini adalah deskriptif kualitatif dengan menggunakan metode linguistik forensik. Data dalam penelitian ini berupa kata, frasa dan kalimat pada akun Kaskus @fufufafa. Hasil penelitian ditemukan sebanyak 58 data yang teridentifikasi mengandung ujaran kebencian berupa penghinaan, pencemaran nama baik, dan memprovokasi, yang menggunakan bentuk lingual seperti umpatan/makian, sindiran, tabu/sarkas. Berdasarkan analisis secara semantik, cuitan @fufufafa mengandung makna yang bersifat negatif, sedangkan secara pragmatik cuitan @fufufafa menunjukkan adanya intensi ilokusi penyerangan yang bertujuan untuk merendahkan dan menghina Prabowo Subianto. Bentuk ujaran kebencian yang paling banyak dominan adalah kategori penghinaan yang menyerang status pribadi, keluarga, fisik, hingga aspek keagamaan Prabowo Subianto. Berdasarkan analisis yang telah dilakukan cuitan @fufufafa bisa berpotensi terhadap konsekuensi hukum dengan pasal 310 KUHP dan pasal 28 (2) UU ITE